Peningkatan Keterampilan Copywriting dan Content Creation bagi Siswa Jurusan Bisnis Daring di SMKN 5 Pandeglang - Ade Ridwan; Bambang Permadi; Maulana Maulana; Laila Natalia; Vinka Sercie Reginata (CV. Denasya Smart Publisher, 2026)
The challenges of the workforce in the digital marketing sector demand the readiness of adaptive practical skills from vocational high school. This community service activity aims to equip students of the Online Business and Marketing (BDP) Department at SMKN 5 Pandeglang with copywriting and promotional content creation skills. The main problem underlying this activity is the low utilization of social media for commercial purposes, where students tend to be passive users rather than structured content producers. The method used is interactive training through a project-based learning approach that includes the delivery of persuasive writing concepts (AIDA and PAS), visual design practices using Canva, and content management simulations. The evaluation results show an increase in students' conceptual understanding and technical skills in composing attractive promotional messages. Through this activity, students successfully developed promotional content drafts for local products such as melinjo chips with better visual and editorial standards. Program sustainability is maintained through the formation of online discussion groups for post-training mentoring.